Effects of clearfelling, slash removal and prescribed burning on amounts of plant nutrients in biomass and soil - Nykvist, Nils (2000)
Total amounts of plant nutrients in biomass: humus and mineral soil were determined in two old Norway spruce ecosystems in central (Garpenberg) and northern Sweden (Flakaträsk). Measurements were repeated 1. 4, 10 and 16 years after clearfelling on plots on which slash was retained, removed or burnt. Half of each plot was planted with Norway spruce, half with Scots pine. Both total and plant-available nutrient elements were determined in the mineral soil to 50cm depth. Different analytical methods for plant available nutrients were used and the relationship between them was calculated. Total amounts of nitrogen in the humus layer and biomass had decreased by ca. 840 kg ha-' four years after clearfelling on plots with retained slash at Garpenberg, and by ca. 840 kg ha-' on burnt plots. Corresponding losses at Flakaträsk were ca. 50 kg and 340 kg N ha-'. Losses of total phosphorus at Garpenberg were ca. 42 and at Flakaträsk 17 kg ha-' on plots with retained slash, ca. 39 and 35 kg ha-' on burnt plots. During thy first four years after clearfelling at Garpenberg, losses of potassium were ca. 100 kg ha both on plots with retained slash and on burnt plots. Corresponding losses at Flakaträsk were ca. 60 and 100 kg ha-'. More than 70% of potassium was lost from burnt plots during the first year after clearfelling at both sites. Clearfelling significantly increased pH (95% confidence) in many humus samples and most samples of mineral soil at both sites. pH generally increased less on plots with slash removed than on those with slash retained, but differences were not significant. Time required for litter to lose its structure in the mor layer was estimated as the quotient between amounts of litter ocularly identified in the mor layer, and litterfall. For needle litter this was 1.7 years at Garpenberg and 4.1 years at Flakaträsk. Thus the litter disintegration rate far exceeded that from other investigations of mass loss of spruce litter in litterbags incubated on the forest floor. Residence times of soil organic carbon, ...